Dromedary (Camelus Dromedarius — OneHumped) And Bactrian (Camelus Bactrianus — Two-Humped) Camels: Differences In Parasitic Diseases And The Main Reasons For These Differences (Wire Insights: Journal of Innovation Insights, 2026)
Parasitic diseases of camels (Camelus dromedarius and Camelus bactrianus), genetic characterization and analysis of their zoonotic risk. Camel farming is an important sector supplying meat, milk and wool to the economies of many countries, especially Uzbekistan and Central Asia. However, parasitic diseases prevalent among camels not only reduce animal productivity but also pose a serious threat to human health